Design, Analysis and Control of Cable-Suspended Parallel Robots and Its Applications - Zi, Bin.; Qian, Sen.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book provides an essential overview of the authors' work in the field of cable-suspended parallel robots, focusing on innovative design, mechanics, control, development and applications. It presents and analyzes several typical mechanical architectures of cable-suspended parallel robots in practical applications, including the feed cable-suspended structure for super antennae, hybrid-driven-based cable-suspended parallel robots, and cooperative cable parallel manipulators for multiple mobile cranes. It also addresses the fundamental mechanics of cable-suspended parallel robots on the basis of their typical applications, including the kinematics, dynamics and trajectory tracking control of the feed cable-suspended structure for super antennae. In addition it proposes a novel hybrid-driven-based cable-suspended parallel robot that uses integrated mechanism design methods to improve the performance of traditional cable-suspended parallel robots. A comparative study on errorand performance indices of hybrid-driven based and traditional cable-suspended parallel robots rounds out the coverage. This book addresses the needs of researchers, engineers and post-graduates in the field of cable-suspended parallel robots and related areas.
Introduction -- Kinematics and dynamics of the feed cable-suspended structure for super antenna -- Trajectory tracking control of the feed cable-suspended structure for super antenna -- Integrated mechanism design and control of the hybrid-driven based cable-suspended parallel robots -- Error analysis of the hybrid-driven based cable-suspended parallel robots -- Performance indices of the hybrid-driven based cable-suspended parallel robots -- Design and dynamics of the cooperative cable parallel manipulators for multiple mobile cranes -- Obstacle avoidance planning of the cooperative cable parallel manipulators for multiple mobile cranes -- Development, coordinated control and experiments of the cooperative cable parallel manipulators for multiple mobile cranes -- Conclusions.
Keywords: Control engineering; Robotics; Automation; Mechanics; Engineering design; Control, Robotics, Automation; Classical Mechanics; Engineering Design